2001
DOI: 10.1177/088626001016011004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Psychological Impact of Chinese Elder Abuse

Abstract: This study examined the prevalence of elder abuse of Chinese in Hong Kong and also assessed its impact on their psychological functioning. A total of 355 (120 males, 235 females) elderly Chinese residing in Hong Kong responded to a questionnaire administered individually. Results indicated prevalence rates of 2% for physical abuse and 20.8% for verbal abuse. These rates were higher than those reported by a telephone survey of similar respondents. Rates did not differ significantly for men and women. Data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
87
5
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 27 publications
14
87
5
4
Order By: Relevance
“…Contrariando, a idéia vigente de que a cultura oriental é marcada pelo respeito e o cuidado aos idosos, observou-se alta prevalência de abuso contra o idoso na China. 22 Essas variações entre as nações remetem a aspectos culturais, mas também indicam a infl uência da qualidade metodológica.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Contrariando, a idéia vigente de que a cultura oriental é marcada pelo respeito e o cuidado aos idosos, observou-se alta prevalência de abuso contra o idoso na China. 22 Essas variações entre as nações remetem a aspectos culturais, mas também indicam a infl uência da qualidade metodológica.…”
Section: Discussionunclassified
“…5,16,18,20,22,23 reportam coefi cientes mais elevados, com prevalências que chegam a quase 50%, como no caso da violência psicológica contra idosos na Finlândia. 5 Esse país apresentou elevado número de maus-tratos.…”
Section: Métodosunclassified
See 1 more Smart Citation
“…For each category, two were male and two were female, except the four males for the 'single male' category and four females for the 'widow' category. These categories and the criteria of identification of elder abuse and neglect have been derived from the researcher's knowledge and observation, as well as from literature found relevant to the issue [1][2][3][4][5][6][7][8][9][10][11][12][18][19][20][21][22][23][24][25][26]. The respondents were from diverse professionals, and only those who agreed to provide information were included in the sample.…”
Section: Methodsmentioning
confidence: 99%
“…18 Other studies in Hong Kong have found the prevalence of EM to be 20%. 19 Despite these studies, there is still a gap in our current understanding of EM in Chinese populations.…”
mentioning
confidence: 99%